Generation of Hydrogen from Zero‐Valent Iron and Water: Catalytic Transfer Hydrogenation of Olefins in Presence of Pd/C. Issue 11 (23rd September 2015) - Patil, Rajendra D.; Sasson, Yoel
Abstract: A non‐hazordous and mild protocol was developed for an efficient reduction of alkenes to alkanes using "iron‐activated water" and catalytic Pd/C (2.5 mol %). Water functions as a hydrogen source without any external acid or base and in the absence of another solvent. The Pd/C catalyst was recovered and recycled. In the course of the reaction zero valent iron is oxidized to magnetite. Abstract : Drawn to it like a magnet : A non‐hazardous and mild protocol was developed for an efficient reduction of alkenes to alkanes using "iron‐activated water" and catalytic Pd/C (2.5 mol %). Water functions as a hydrogen source without any external acid or base and in the absence of another solvent. The Pd/C catalyst was recovered and recycled. In the course of the reaction zero valent iron is oxidized to magnetite.